2005
DOI: 10.1038/sj.mp.4001701
|View full text |Cite
|
Sign up to set email alerts
|

The phenotypes of bipolar disorder: relevance for genetic investigations

Abstract: The search for susceptibility genes for bipolar disorder (BD) depends on appropriate definitions of the phenotype. In this paper, we review data on diagnosis and clinical features of BD that could be used in genetic studies to better characterize patients or to define homogeneous subgroups. Clinical symptoms, long-term course, comorbid conditions, and response to prophylactic treatment may define groups associated with more or less specific loci. One such group is characterized by symptoms of psychosis and lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
68
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(73 citation statements)
references
References 262 publications
4
68
0
1
Order By: Relevance
“…Bipolar disorder has been shown to be highly heritable mental illness (McGuffin et al, 2003), with linkage studies supporting a complex polygenic basis for the condition (Craddock & Jones, 1999). Additionally, phenotypic heterogeneity associated with diaphanous diagnostic boundaries of the bipolar disorder spectrum has been recognized as a major obstacle in the genetic dissection of the illness (Hasler et al, 2006;MacQueen et al, 2005). Consequently, it has been suggested that genetic and clinical work might consider whether all phenotypic variants of the bipolar spectrum are an expression of a continuous underlying genetic liability (Edvardsen et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Bipolar disorder has been shown to be highly heritable mental illness (McGuffin et al, 2003), with linkage studies supporting a complex polygenic basis for the condition (Craddock & Jones, 1999). Additionally, phenotypic heterogeneity associated with diaphanous diagnostic boundaries of the bipolar disorder spectrum has been recognized as a major obstacle in the genetic dissection of the illness (Hasler et al, 2006;MacQueen et al, 2005). Consequently, it has been suggested that genetic and clinical work might consider whether all phenotypic variants of the bipolar spectrum are an expression of a continuous underlying genetic liability (Edvardsen et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The suggestive peaks at 4q and 13q are consistent with significant linkage results previously reported by our group in independent Australian BP cohorts, 32,42 while the 6q locus was reported as one of two confirmed BP loci in a genome-wide meta-analysis of 1067 families. 43 The supplementary markers were added to confirm the genome-wide linkage to 15q, and to gain greater location estimates for a BP susceptibility gene around the maximal genome scan marker D15S130. Using Australian allele frequencies for the additional markers, a significant two-point LOD score of 3.38 was identified at marker D15S130.…”
Section: Discussionmentioning
confidence: 99%
“…The quoted prevalence for BD is approximately one percent of the population (Spearing, 2001), although several factors probably result in under-or misdiagnosis. First, there are many BD phenotypes, complicating diagnosis (Thomas, 2004;MacQueen et al, 2005). Second, from these multiple phenotypes several variants exist in which one or other phase is extremely mild.…”
Section: Introductionmentioning
confidence: 99%